Generalized Heat Equation Under Conform Derivative - Elomari, M’hamed; Melliani, Said; Chadli, Lalla Saadia (Sarajevo Journal of Mathematics, 2020)
In the present work, we establish the existence and uniqueness result of the linear heat equation with Conform derivative in Colombeau generalized algebra. We using for the first time the notion of a generalized conformable semigroup and the purpose of introducing Conform derivative is regularizing it in Colombeau.